2020
DOI: 10.5194/acp-20-181-2020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and uncertainty investigation of the NO<sub>2</sub>, CO and NH<sub>3</sub> modeling over China under the framework of MICS-Asia III

Abstract: Abstract. Despite the significant progress in improving chemical transport models (CTMs), applications of these modeling endeavors are still subject to large and complex model uncertainty. The Model Inter-Comparison Study for Asia III (MICS-Asia III) has provided the opportunity to assess the capability and uncertainty of current CTMs in East Asian applications. In this study, we have evaluated the multi-model simulations of nitrogen dioxide (NO2), carbon monoxide (CO) and ammonia (NH3) over China under the fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 108 publications
2
39
0
Order By: Relevance
“…For example, for SO 2 , all models estimated more deposition than anthropogenic emissions in Japan. Previous studies based on source-receiver relationships in model experiments indicated the importance of volcanic sources and transboundary air pollution for S over Japan (Kajino et al, 2011;Kuribayashi et al, 2012;Itahashi et al, 2017;Itahashi, 2018). Over north Asia (Mongolia and Russia), all models simulated more deposition than emissions; deposition was predicted to be 1.9 and 2.5 times higher than emissions over Mongolia and Russia, respectively, by model M2, which estimated the lowest total deposition.…”
Section: Total Deposition Mapping Over Asiamentioning
confidence: 78%
“…For example, for SO 2 , all models estimated more deposition than anthropogenic emissions in Japan. Previous studies based on source-receiver relationships in model experiments indicated the importance of volcanic sources and transboundary air pollution for S over Japan (Kajino et al, 2011;Kuribayashi et al, 2012;Itahashi et al, 2017;Itahashi, 2018). Over north Asia (Mongolia and Russia), all models simulated more deposition than emissions; deposition was predicted to be 1.9 and 2.5 times higher than emissions over Mongolia and Russia, respectively, by model M2, which estimated the lowest total deposition.…”
Section: Total Deposition Mapping Over Asiamentioning
confidence: 78%
“…We estimated the model uncertainties from meteorology to be ∼ ±16 % by simulating the surface BC concentrations under conditions with negligible wet deposition and considering both the horizontal and vertical inhomogeneities in the model and the spread of multimodel simulations of CO over the East China Sea (Kong et al, 2020). The uncertainty was assumed to have been equally contributed by the systematic and random terms (±12 %).…”
Section: Methodsmentioning
confidence: 99%
“…Lelieveld et al (2015) estimated that over 3 million premature deaths could be attributable to outdoor air pollution worldwide in 2010 based on their analysis of data and the results from a high-resolution global air quality model. Since the turn of the 21st century, East Asia has undergone remarkable changes in air quality as observed by satellite and ground stations (Jin et al, 2016;Krotkov et al, 2016). In the past decade, haze (fine particle) pollution has become a household name in China and many severe haze events have been reported and their formation mechanisms and associations with global-and meso-scale meteorology have been analyzed (Zhao et al, 2013;Huang et al, 2014;Gao et al, 2016;Cai et al, 2017;Zou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%